Assessment of Power and Torque Delivery Profiles in a Small-Displacement Engine Following Bore Modifications - BIN MOHAMMAD FARID, MOHAMAD YAZID; PROF. Dr. AHMAD JAIS BIN ALIMIN (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This project focuses on the repair, calibration, and performance evaluation of a motorcycle chassis dynamometer to ensure accurate and reliable engine testing, specifically for the Yamaha Y15ZR. The dynamometer initially exhibited mechanical wear, sensor malfunctions, and calibration drift, resulting in inconsistent torque, power, and RPM readings. Through systematic troubleshooting and covering mechanical realignment, electrical repairs, and sensor recalibration in the system was restored to proper working condition. A calibrated testing setup was then used to establish baseline engine performance data, followed by comparative tests using two different flat-top ceramic pistons (57 mm and 63mm). The use of ceramic pistons, known for high thermal resistance and low heat conductivity, allowed the study to examine variations in combustion efficiency, heat transfer characteristics, and emission behavior across different piston sizes. Preliminary results show improved combustion stability and measurable changes in power output and exhaust temperature corresponding to piston diameter. Overall, this project provides a functional dynamometer platform and meaningful insights into how piston geometry and material influence motorcycle engine performance, supporting future tuning, research, and development efforts